Petrography, metamorphism, deformation and P-T conditions in the western arm of the Lufilian Arc - Zambezi, north-western Zambia - Chilekwa, Mwango (Rhodes University, Faculty of Science, Department of Geology, 2020)
The Zambezi area in north-western Zambia is underlain by Neoproterozoic Katanga Supergroup and older, Archean to Mesoproterozoic Basement Supergroup rocks. The area lies within the Domes Region, which is a structural domain of the Lufilian Arc. The stratigraphic succession within Zambezi area is dominated by the Grand Conglomerate Formation (GC) and Mwashia Group which are the most extensive units, and the less abundant Lower and Upper Roan Groups of the Katanga Supergroup. They wrap around the domal Basement Supergroup units. The mineral assemblage of the Mwashia and the GC schists commonly contains garnet, anthophyllite and biotite. GC rocks show remnants of primary structures such as clasts and sedimentary features. Anthophyllite, garnet and biotite are the dominant Mg-Fe rich metamorphic minerals. However, these are iron rich for each mineral phase and has been attributed to iron rich protoliths. The earliest recognised deformation episode (D1) formed NE-SW S1 foliations within GC which is consistent with the regional structural trend in the western Lufilian Arc. S1 was later affected by D2 that generated downward facing F2 folds and S2 foliations. The other associated feature to D2 is garnet that grew as the result of pro-grade metamorphism. The D3 deformation fabric is not developed and did not affect much of the structural geometry of the Zambezi area. The peak assemblages of the Basement Supergroup and the Katanga Supergroup formed at mid-amphibolite facies conditions of 590 °C and 630 °C at an average pressure of 4.0 kbar. The Basement Supergroup has undergone retrograde metamorphism to greenschist facies condition indicated by presence of chlorite and also determined by biotite-anorthite isopleth in THERIAK DOMINO. At the eastern part of Zambezi area, the Katanga Supergroup rocks were retrogressed in the upper greenschist facies at about ~470°C and ~4.0 kbar due to isobaric cooling.
Keywords: Petrogenesis -- Zambia -- Zambezi District; Metamorphism (Geology) -- Zambia -- Zambezi District; Petrology -- Zambia -- Zambezi District; Formations (Geology) -- Zambia -- Zambezi District; Rock deformation -- Zambia -- Zambezi District; Lufilian Arc; Neoproterozoic Katangan R.A.T. (Roches Argilo Talqueuse) Subgroup